2016
DOI: 10.7717/peerj.2762
|View full text |Cite
|
Sign up to set email alerts
|

Selective enhancement of attentional networks in college table tennis athletes: a preliminary investigation

Abstract: The purpose of the study was to investigate the characteristics of the attentional network in college table tennis athletes. A total of 65 college students categorized as table tennis athlete group or non-athlete group participated in the study. All participants completed the attentional network test (ANT) which measured the alerting, orienting and executive control networks. The results showed a significant difference between the athlete and non-athlete group for executive control network (p < 0.01), while no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 25 publications
6
28
1
1
Order By: Relevance
“…To strengthen the effect of selective enhancement, ROC analysis showed that the executive network had a larger power than the alerting and orienting network at discriminating between open-skill exercisers and the controls in older adults. These results are similar with a previous study showing that college-level table tennis athletes exhibit selectively enhanced executive control of the attentional networks (Wang, Guo & Zhou, 2016). Thus, the selective enhancement of the executive control network of open-skill exercise occurs in both younger and older adults.…”
Section: Discussionsupporting
confidence: 91%
“…To strengthen the effect of selective enhancement, ROC analysis showed that the executive network had a larger power than the alerting and orienting network at discriminating between open-skill exercisers and the controls in older adults. These results are similar with a previous study showing that college-level table tennis athletes exhibit selectively enhanced executive control of the attentional networks (Wang, Guo & Zhou, 2016). Thus, the selective enhancement of the executive control network of open-skill exercise occurs in both younger and older adults.…”
Section: Discussionsupporting
confidence: 91%
“…To strengthen the effect of selective enhancement, ROC analysis showed that the executive network had a larger power than the alerting and orienting network at discriminating between open-skill exercisers and the controls in older adults. These results are similar with a previous study showing that college-level table tennis athletes exhibit selectively enhanced executive control of the attentional networks(Wang et al 2016). Thus, the selective enhancement of the executive control network of open-skill exercise occurs in both younger and older adults.…”
supporting
confidence: 91%
“…ANT has been used by previous studies to show the positive effects of martial arts training (Johnstone & Marí-Beffa 2018), table tennis training (Wang et al 2016), chronic exercise (Pérez et al 2014), and acute bouts of aerobic exercise (Chang et al 2015;Huertas et al 2011)…”
Section: Introductionmentioning
confidence: 99%
“…The findings implied that the motor skill training would shorten the link-step distance to accelerate the reaction, movement planning and execution with high attentional demands (Wolf et al, 2014). This is especially important for the fast-pace racket athletes of badminton and table tennis (van de Water et al, 2017;Wang, Guo, & Zhou, 2016a).…”
Section: Optimal Connectivity Distance Differences Between Athletesmentioning
confidence: 99%